United States, portrait of Iñupiat man in Utqiaġvik - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1959)
Close portrait of native man with hood down. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3